The use of moderately hypofractionated post-operative radiation therapy for breast cancer in clinical practice: A critical review. (December 2020) - Marta, Gustavo Nader; Coles, Charlotte; Kaidar-Person, Orit; Meattini, Icro; Hijal, Tarek; Zissiadis, Yvonne; Pignol, Jean-Philippe; Ramiah, Duvern; Ho, Alice Y.; Cheng, Skye Hung-Chun; Sancho, Gemma; Offersen, Birgitte Vrou; et al.
Highlights: Moderately hypofractionated radiation therapy (mHF-RT) for breast cancer patients is applied very variably in clinical practice worldwide. mHF-RT to the breast, chest wall (+/− reconstruction), and regional lymph nodes is a safe and effective regimen. The use of mHF-RT can help to compensate the potential backlog of patients whose radiation therapy was delayed. Abstract: Post-operative radiation therapy (RT) reduces loco-regional recurrence rates and mortality in most patients with non-metastatic breast cancer. The aim of this critical review is to provide an overview of the applicability of moderately hypofractionated RT for breast cancer patients, focusing on factors influencing clinical decision-making. An international group of radiation oncologists agreed to assess, integrate, and interpret the existing evidence into a practical report to guide clinicians in their daily management of breast cancer patients. We conclude that moderately hypofractionated RT to the breast, chest wall (with/without breast reconstruction), and regional lymph nodes is at least as safe and effective as conventionally fractionated regimens and could be considered as the treatment option for the vast majority of the patients.For those who are still concerned about its generalised application, we recommend participating in ongoing trials comparing moderately hypofractionated RT to conventionally fractionated RT for breast cancer patients in some clinical circumstances.